Dietary intake of protein from different sources and weight regain, changes in body composition and cardiometabolic risk factors after weight loss: the DIOGenes study - Baak, v; Larsen, T; Jebb, S; Martinez, A; Saris, W; Handjieva-Darlenska, T; Kafatos, A; Pfeiffer, A; Kunesova, M; Astrup, A (MDPI, 2017)
An increase in dietary protein intake has been shown to improve weight loss maintenance in the DIOGenes trial. Here, we analysed whether the source of the dietary proteins influenced changes in body weight, body composition, and cardiometabolic risk factors during the weight maintenance period while following an energy-restricted diet. 489 overweight or obese participants of the DIOGenes trial from eight European countries were included. They successfully lost >8% of body weight and subsequently completed a six month weight maintenance period, in which they consumed an ad libitum diet varying in protein content and glycemic index. Dietary intake was estimated from three-day food diaries. A higher plant protein intake with a proportional decrease in animal protein intake did not affect body weight maintenance or cardiometabolic risk factors. A higher plant protein intake from non-cereal products instead of cereal products was associated with benefits for body weight maintenance and blood pressure. Substituting meat protein for protein from other animal sources increased insulin and HOMA-IR (homeostasis model assessment of insulin resistance). This analysis suggests that not only the amount of dietary proteins, but also the source may be important for weight and cardiometabolic risk management. However, randomized trials are needed to test the causality of these associations.